Adverse Drug Reactions Related to Treatment of Drug-Susceptible Tuberculosis in Brazil: A Prospective Cohort Study - Sant´Anna, Flávia M.; Araújo-Pereira, Mariana; Schmaltz, Carolina A. S.; Arriaga, María B.; de Oliveira, Raquel V. C.; Andrade, Bruno B.; Rolla, Valeria C. (Frontiers in Tropical Diseases, 2022)
Standard anti-tuberculosis treatment is highly effective, but a great challenge is the management of adverse drug reactions (ADR). Our study aimed to characterize ADR according to type, severity and time of occurrence. A prospective tuberculosis (TB) cohort has been followed, from 2010 to 2016, at a reference center in Rio de Janeiro, Brazil. Clinical and laboratory tests information were collected in all visits. ADR were described according to the affected organ/system, classified as clinical and/or laboratorial, early (first 2 months) or late. ADR’s causality and intensity were assessed. In our study 552 patients were included, 78.8% presented at least one ADR, 34% were people living with HIV (PLHIV). Most ADR were clinical (53%), early (82.5%), mild/moderate (88.7%) events and of “metabolic and nutritional disorders” category. There were no significant differences in type, severity or causality between “early” and “late” groups. However, “early” group presented a higher frequency of “metabolic and nutritional disorders” (27.8%) and “gastrointestinal system disorders” (23.5%), while “skin and appendages disorders” were more frequent in the “late” group. ADR are frequent and occur at any time during treatment, although the majority are early and grade and not severe.